2014
DOI: 10.1113/jphysiol.2014.275545
|View full text |Cite
|
Sign up to set email alerts
|

PGC1‐α over‐expression prevents metabolic alterations and soleus muscle atrophy in hindlimb unloaded mice

Abstract: Key pointsr Oxidative stress is widely considered a major cause of muscle loss not only in disuse but also in most chronic diseases, triggering carbonylation of proteins and activation of catabolic pathways involved in their degradation.r Here we show that administration of an antioxidant prevents redox imbalance, but does not prevent activation of catabolic pathways and muscle atrophy.r We indicate that alterations of oxidative metabolism, occurring in slow soleus muscle, are not just a consequence of disuse,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
223
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 197 publications
(246 citation statements)
references
References 76 publications
18
223
1
4
Order By: Relevance
“…It was previously demonstrated that maximal expression of both MuRF1 and MAFbx is reached after 3 days of unloading (Cannavino et al. 2014; Shenkman et al. 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It was previously demonstrated that maximal expression of both MuRF1 and MAFbx is reached after 3 days of unloading (Cannavino et al. 2014; Shenkman et al. 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The few studies conducted in human observed that carbonylated protein levels did not change in the vastus lateralis after 8 and 14 days of bed rest [66,67], but became higher after 35 days [66]. In rodents, some studies reported an increase of carbonylated proteins in the soleus during the first week of hindlimb unloading [57,[68][69][70], whereas other reports did not observed such effect after 3, 7 and 14 days of hindlimb unloading [53,60,62]. A more restricted number of studies focused on the effects of immobilization on α,β-unsaturated aldehydes (e.g., 4-HNE, MDA), markers of lipid peroxidation.…”
Section: Skeletal Muscle Oxidative Stress In Immobilization and Physimentioning
confidence: 93%
“…On one hand, the ratio GSH/GSSG decreases in skeletal muscle during hindlimb unloading [59][60][61]. On the other hand, immobilization causes, in skeletal muscle, an increase of SOD1 and catalase protein content and activities [53,57,59,[61][62][63][64], whereas SOD2 protein content and activity do not change [61,[63][64][65].…”
Section: Skeletal Muscle Oxidative Stress In Immobilization and Physimentioning
confidence: 98%
See 2 more Smart Citations